Effects of oxygen on responses to heating in two lizard species sampled along an elevational gradient. (August 2017) - DuBois, P. Mason; Shea, Tanner K.; Claunch, Natalie M.; Taylor, Emily N.
Abstract: Thermal tolerance is an important variable in predictive models about the effects of global climate change on species distributions, yet the physiological mechanisms responsible for reduced performance at high temperatures in air-breathing vertebrates are not clear. We conducted an experiment to examine how oxygen affects three variables exhibited by ectotherms as they heat—gaping threshold, panting threshold, and loss of righting response (the latter indicating the critical thermal maximum)—in two lizard species along an elevational (and therefore environmental oxygen partial pressure) gradient. Oxygen partial pressure did not impact these variables in either species. We also exposed lizards at each elevation to severely hypoxic gas to evaluate their responses to hypoxia. Severely low oxygen partial pressure treatments significantly reduced the gaping threshold, panting threshold, and critical thermal maximum. Further, under these extreme hypoxic conditions, these variables were strongly and positively related to partial pressure of oxygen. In an elevation where both species overlapped, the thermal tolerance of the high elevation species was less affected by hypoxia than that of the low elevation species, suggesting the high elevation species may be adapted to lower oxygen partial pressures. In the high elevation species, female lizards had higher thermal tolerance than males. Our data suggest that oxygen impacts the thermal tolerance of lizards, but only under severely hypoxic conditions, possibly as a result of hypoxia-induced anapyrexia. Highlights: Lizards exposed to hypoxic air exhibited reduced lower thermal tolerance. Under hypoxia, partial pressure of oxygen was positively related to thermal tolerance. Hypoxia especially impacted thermal tolerance of a low elevation species. Female lizards had higher thermal tolerance than males.